Establishment of High-Throughput Screening Assay using 384-Well Plate for Identification of Potent Antioxidants from Malaysian Local Plants Repository and Phytochemical Profile of Tetracera scandens - Amyra Amat Sain,; Azimah Amanah,; Mohd Hasnan Mohd Noor,; Wai Kwan Lau,; Olalere Olusegun Abayomi ,; Zafarina Zainuddin, (Tropical Life Sciences Research, 2025)
The increasing prevalence of chronic diseases and oxidative stress-related conditions has led to a growing interest in natural products with potent antioxidant properties. High-throughput screening (HTS) assays offer a promising solution for the rapid evaluation of numerous samples. This study aims to establish a robust HTS assay using the 2-Diphenyl-1-Picrylhydrazyl (DPPH) method to identify natural products with significant antioxidant capabilities, ensuring their safety profiles through cytotoxicity screening and phytochemical profiling. An automated liquid handler with the usage of a 384-well assay plate was employed in optimising and validating the 2,2-diphenyl-1-picrylhydrazyl (DPPH)-HTS assay by calculating the metrics. The HTS metrics include Z-prime (Z’) values of 0.72 and 0.63, signal to background (S/B) ratios of 3.54 and 9.02, and coefficient of variation percentages (%C/V) of 4.25 and 6.49 for each primary and secondary screenings, respectively. These values indicated that the HTS assay was excellent. By using optimised HTS-DPPH assay programme, a total of 363 plant extracts were screened and 58 (16%) were found to have potent antioxidant activity (a ‘yes’ score and EC50 < 50 ?g/mL). Out of these 363 extracts, only 80 plants were identified with herbarium and the screening results revealed that Tetracera scandens along with other 11 plants have potent antioxidant activities. T. scandens was the most potent and the methanol extract from its leaves recorded an EC50 value of 13.041± 0.82 ?g/mL. However, the aqueous extract of T. scandens leaves (TSLAE) was selected to allow any possibilities of using it for traditional herbal preparation. TSLAE presented an EC50 value of 13.76 ± 4.50 ?g/mL in the DPPH assay and was non-toxic towards normal cells with an IC50 value of > 100 ?g/mL. Secondary metabolites with promising antioxidant potentials were successfully identified using LC/MS and the library, which were mainly flavonoids (37.5%), phenolics (8.9%) and polyphenols (8.9%). HTS-DPPH is a robust and rapid technique for screening of antioxidative substances in plant extracts. The hit is non-toxic in vitro and rich in secondary metabolites that contribute to antioxidant activity.